Adsorption properties and competitive adsorption mechanism exhibited by carbon-nanotube-modified biochar for removal of crude oil and Ni(II) pollutants from water - Di Cao; Ruiyan Niu; Guanglu Mo; Huiwen Deng; Rui Liu; Jie Liu; Jialin Fan (Ecotoxicology and Environmental Safety)
Carbon-nanotube-modified biochar (CNT3-CBC) with a nanostructured surface was prepared by using cattle manure as the raw material via the impregnation method. This modified biochar was then used to adsorb petroleum and Ni(II) from aqueous solutions. Various physicochemical characterization techniques were employed, including SEM, BET analysis, FTIR, and XPS. Kinetic and isothermal adsorption characteristics were analyzed. The influence of different biochar dosages, solution pH levels, and number of adsorption cycles on the efficiency of removal of crude oil and Ni(II) was meticulously evaluated. Results indicated that modified biochar had a higher surface area, a greater number of surface functional groups, and higher interaction forces compared to biochar. Adsorption kinetics and isotherms showed that modified biochar had a strong adsorption capacity. The experimental data conformed closely to the Elovich, Langmuir, and Freundlich adsorption models, underscoring the significant contributions of both physical and chemical adsorption mechanisms. Competitive adsorption of modified biochar in the co-sorption of petroleum and nickel solutions exists, and the modified biochar demonstrated high capacities for crude oil and Ni(II) in the competitive adsorption. The modified biochar prepared at a pyrolysis temperature of 800°C exhibited a superior adsorption performance, and the adsorption capacities of crude oil and Ni(II) were 303.03 mg·g−1 and 32.87 mg·g-¹ , respectively. Modified biochar has better regeneration potential after crude oil and Ni(II) adsorption, with the removal efficiency remaining above 50 % in the fourth cycle. As an efficient and environmentally friendly adsorbent, modified biochar shows great potential for removing crude oil and Ni(II) pollutants from water.